Subjective social status moderates back pain and mental health in older men. (3rd April 2022) - Mu, Christina; Jester, Dylan J.; Cawthon, Peggy M.; Stone, Katie L.; Lee, Soomi
Abstract: Objectives: Back pain and poor mental health are interrelated issues in older men. Evidence suggests that socioeconomic status moderates this relationship, but less is known about the role of subjective social status (SSS). This study examined if the association between back pain and mental health is moderated by SSS. Method: We used a sample of community-dwelling older men (≥65 years) from the Osteoporotic Fractures in Men Study ( N = 5994). Participants self-reported their back pain severity and frequency over the past 12 months. SSS was assessed with the MacArthur Scale of SSS. Mental health was assessed with the SF-12 Mental Component Summary (MCS). Results: Severe back pain was associated with lower SF-12 MCS scores ( p = .03). Back pain frequency was not associated with SF-12 MCS scores. SSS moderated the back pain and mental health relationship. Among men with higher national or community SSS, the association between back pain severity and SF-12 MCS scores was not significant. However, among men with lower national or community SSS, more severe back pain was associated with lower SF-12 MCS scores ( p ' s < .001). Among those with lower national or community SSS, greater back pain frequency was also associated with lower SF-12 MCS scores ( p ' s < .05). Conclusion: Where one ranks oneself within their nation or community matters for the back pain and mental health relationship. Higher SSS may be a psychosocial resource that buffers the negative associations of severe and frequent back pain on mental health in older men.